The magic locket - Koda-Callan, Elizabeth (New York : Workman Pub., 1988)
A girl who cannot do anything right is discouraged, until her favorite great-aunt gives her a "magic" locket that gives her self-confidence.
Keywords: Self-confidence; Great-aunts